Impacts of Historical Land Use Changes on Ecosystem Services in Guangdong Province, China - Haizhen Chen; Yi Chen; Xiaosong Chen; Xingzhong Zhang; Haowei Wu; Zhihui Li (Land, 2022)
Assessing land use change and its impacts on ecosystem services is of great significance for optimizing land use management and enhancing ecosystem sustainability. This study explores land use changes and their impacts on five typical ecosystem services, namely grain production (GP), water yield (WY), soil conservation (SC), habitat quality (HQ), and carbon sequestration (CS), during 1990–2020 using the Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) model in Guangdong province, which has experienced substantial land use change. During the study period, cultivated land, forest land, grassland, water areas, built-up land, and unused land correspondingly had changed by −10.7%, −1.9%, −5.1%, 13.7%, 97.9%, and −38.8%. For ecosystem services, the GP, SC, and HQ averagely decreased by −8.66% (−12.3 t·km−2), −0.02% (−2 t·km−2), and−2.74% (−0.02), respectively, while WY and CS increased by 3.10% (22 mm) and 20.70% (515 t·km−2), respectively. Land use changes that had the greatest average negative impacts on GP, WY, SC, HQ, and CS were cultivated land to built-up land (−150.9 t·km−2), unused land to water areas (−1072 mm), grassland to unused land (−10,166 t·km−2), forest land to built-up land (−0.65), and forest land to water areas (−2974 t·km−2) respectively, and that had the greatest average positive impacts were grassland to cultivated land (78.8 t·km−2), water areas to built-up land (943 mm), unused land to forest land (3552 t·km−2), built-up land to forest land (0.40), and water areas to forest land (3338 t·km−2), respectively. The results indicated that land use and its changes had a significant impact on ecosystem services.